Images of Arabs and Islam in Burton’s Pilgrimage to Al-Madinah and Meccah - السعدون، عبدالكريم محمد; ناش، جيفري (المركز القومي للبحوث بغزة, 2023)
هدفت الدراسة إلى مناقشة مكانة العرب والإسلام في الثقافة الغربية مع التركيز على البريطانيين في العصر الفيكتوري الذين اهتم مفهومهم الرئيسي لشبه الجزيرة العربية بالصحراء والشرق الغريب أدى الاهتمام السياسي والاقتصادي المتزايد للحكومة البريطانية في شبه الجزيرة العربية إلى زيادة التركيز على العرب المسلمين في الشرق الأدنى وشبه الجزيرة العربية، بدءا من غزو نابليون لمصر عام 1799م، حيث تصاعدت حدة العلاقة بين السويس والإمبراطورية العثمانية والإمبراطورية البريطانية. عليه ذهبت بعثات وجولات لأسباب مختلفة إلى الشرق الأدنى وشبه الجزيرة العربية لاكتشاف وتقديم المعلومات للإمبراطوريات الغربية وخاصة تلك التي برعاية الجمعية الجغرافية الملكية. كما جاء الكم المتزايد من العلوم المتعلقة بالعالم العربي تحت مظلة الاستشراق، بما في ذلك جميع الكتاب والروائيين ورواد الرحلات المهتمين بـ "الشرق". كان بيرتون من الرحالة المستشرقين، والذي كانت مهمته لزيارة الحرمين الشريفين المدينة المنورة ومكة المكرمة مهمة كلاسيكية ورومانسية لم تكن مهمة بيرتون مجرد تزويد رعاته بالمعلومات الجغرافية والعلمية عن السويس وشبه الجزيرة العربية والحرمين، ولكن كانت لديه دوافع شخصية أخرى أثرت على عمله الرواية الشخصية للحج إلى المدينة المنورة ومكة المكرمة. اتبعت هذه الدراسة المنهج الاستقصائي ومنهج التحليل الوصفي ومنهج التحليل النقدي للإجابة على أسئلة الدراسة. وتكونت هذه الدراسة من أربعة أقسام. قدم القسم الأول مقدمة جاء فيها مشكلة الدراسة وفرضياتها وأهميتها ومن ثم المناهج المتبعة في هذه الدارسة وأخيرا خطة البحث القسم الثاني قدم آراء الانجليز في العصر الفيكتوري عن المسلمين في ثلاثة أجزاء: الأول: الفكر الفيكتوري والثقافة في بريطانيا. الثاني: الإسلام في الأدب الفيكتوري. وفي الثالث الرحلات الفيكتورية. كما تضمن القسم الثالث تحليلا موضوعيا لرحلة بيرتون مع التركيز على اهتمامات بيرتون الليبرالية والإنثربيولوجية التي حفزت إمبرياليته. وأخيرا القسم الرابع خاتمة الدراسة، حيث اشتمل على النتيجة النهائية للدراسة مع ذكر الحدود المكانية والزمانية لها وتوصيات لدراسات مستقبلية عن كتاب السير ريتشارد بيرتون. The study aimed to discuss the position of Arabs and Islam in Western culture, concentrating on the British Victorians whose main conception of Arabia concerned the desert and the exotic orient. The increasing political and economic interest of the British government in Arabia led to more focus on Muslim Arabs in the Near East and the Arabian Peninsula, beginning with Napoleon’s conquest of Egypt c. 1799, and escalating as Suez and the Ottoman Empire became more intertwined with the British imperialism. Missions and tours for various reasons went to the Near East and the Arabian Peninsula to discover and bring information for the Western Empires specially, the Royal Geographical Society. On the other hand, the growing body of science concerning the Arab world came under the umbrella of orientalism, including all writers, novelists and travelogues concerned with ‘the orient’. One of the oriental travellers was Burton, whose mission to visit the two Islamic holy places Al-Madinah and Mecca was a classic and romantic one. Burton’s mission was not only to supply his sponsors with geographical and scientific information about Suez, the Arabian Peninsula and the two holy places, but he had other personal motivations that affected his work; Personal Narrative of A Pilgrimage to Al-Madinah and Meccah. Continuously, the study applies investigative, descriptive analysis and critical analysis methods to answer the above questions. The study consists of four sections. Section one presents an introduction in five subsections: problem of the study, hypotheses of the study, significance of the study, methodology of the study and finally, structure of the study. Section two presents Victorians’ views of Muslims in three subsections: Victorian thinking and culture in Britain; Islam in the Victorian literature; and Victorian travelogues. Section three comprises a thematic analysis of Burton's Pilgrimage, concentrating on his liberal and ethnographic interests that motivated his imperialism. At the last section, the study discusses the final results, the study limitations and recommendations for the studies about Burton.
Keywords: أدب الرحلات -- الثقافة الغربية -- العصر الفيكتوري -- شبه الجزيرة العربية